2017
DOI: 10.3389/fpubh.2017.00209
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Oral Health Education Improves Knowledge, Confidence, and Practice for Pediatric Healthcare Providers

Abstract: Dental caries is the most prevalent chronic childhood disease in the United States. Dental caries affects the health of 60–90% of school-aged children worldwide. The prevalence of untreated early childhood dental caries is 19% for children 2–5 years of age in the U.S. Some factors that contribute to the progression of dental caries include socioeconomic status, access to dental care, and lack of anticipatory guidance. The prevalence of dental caries remains highest for children from specific ethnic or racial g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
39
5
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 19 publications
9
39
5
4
Order By: Relevance
“…This study shows that students significantly improved in their knowledge, confidence, and attitude on children's oral health after completion of the course. This is similar to previous studies where interprofessional education increased participants' knowledge, confidence, and attitudes in children's oral health [11,17]. This suggests that incorporating interdisciplinary training early on in the providers' career can be a promising strategy in integrating children's oral health care into primary care practices.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This study shows that students significantly improved in their knowledge, confidence, and attitude on children's oral health after completion of the course. This is similar to previous studies where interprofessional education increased participants' knowledge, confidence, and attitudes in children's oral health [11,17]. This suggests that incorporating interdisciplinary training early on in the providers' career can be a promising strategy in integrating children's oral health care into primary care practices.…”
Section: Discussionsupporting
confidence: 86%
“…A moderate correlation was found between students' improvement in knowledge and their actual clinical skills. Other studies on interprofessional children's oral health education also involved a combination of didactics and clinical simulations; however, limited studies measured participants' clinical skills objectively on a set criterion [11,17,18,28]. No significant correlation was found between students' improvement in confidence and attitude and their clinical skills.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some previous studies regarding oral health interprofessional education for nursing students reported that students' attitudes and confidence regarding oral health improved after the education intervention (Cooper et al, 2017;Golinveaux et al, 2013). Therefore, interprofessional education with dental and nursing staff may be effective for improvement of attitude and confidence.…”
Section: Discussionmentioning
confidence: 96%
“…Oral hygiene education, like any other type of health education, encounters the problem of knowledge retention [39]. A short, focused oral hygiene education program had a significant impact on physician assistants' retention rate of oral hygiene knowledge [40]. The key elements of improving learning retention rates include drawing the learner's attention, stimulating interest in the topic, arousing motivation for learning, and building ways for learners to critically think about information [41].…”
Section: Lasting Effects Of the Oral Hygiene Educationmentioning
confidence: 99%